Big bottlenecks in cardiovascular tissue engineering. (December 2018) - Huang, Ngan; Serpooshan, Vahid; Morris, Viola; Sayed, Nazish; Pardon, Gaspard; Abilez, Oscar; Nakayama, Karina; Pruitt, Beth; Wu, Sean; Yoon, Young-sup; Zhang, Jianyi; Wu, Joseph
Abstract Although tissue engineering using human-induced pluripotent stem cells is a promising approach for treatment of cardiovascular diseases, some limiting factors include the survival, electrical integration, maturity, scalability, and immune response of three-dimensional (3D) engineered tissues. Here we discuss these important roadblocks facing the tissue engineering field and suggest potential approaches to overcome these challenges. In this Comment, Ngan Huang et al. discuss recent advances in cardiovascular tissue engineering and some of the main challenges that remain in translating these advances to the clinic. The authors propose future direction for the field to focus research efforts.